Pengaruh Efektivitas Penerapan Sistem Informasi Akuntansi, Pemanfaatan Teknologi Informasi dan Motivasi Kerja Pada Kinerja Individu - Dewi Sapitri, Ni Luh Gede; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
The use of information technology in government agencies can help employees work effectively and efficiently. The purpose of this study is to determine the effect of the effectiveness of the application of accounting information systems, technology utilization and work motivation on individual performance. The method of research used in this study is quantitative associative approach. This research was conducted at the Tabanan Regency Regional Finance Agency (Bakeuda). This study uses a sampling method with purposive sampling, namely sampling techniques with certain considerations or criteria. The number of samples used was 103 respondents.Based on the results of the analysis, it was found that the effectiveness of the application of AIS, utilization of information technology and work motivation had a positive effect on individual performance at Bakeuda Tabanan. Keywords:  The effectiveness of the application of accounting information system, technology Utilization, motivation work,  individual performance.